Cattaneo-Christov heat flux and entropy generation on hybrid nanofluid flow in a nozzle of rocket engine with melting heat transfer. (December 2021) - Waqas, Hassan; Muhammad, Taseer; Noreen, Sobia; Farooq, Umar; Alghamdi, Metib
Abstract: This study aims to scrutinize the mathematical formulations of hybrid nanoliquid filled with thermal radiation, Cattaneo-Christov heat theory and melting phenomenon in a nozzle of rocket engine that includes hybrid nanoparticles ( C o F e 2 O 4, C d T e, T i O 2, C u & C u O ) and kerosene ( C 12 H 26 − C 15 H 32 ) utilized as a base fluid. The main governing equations are changed into a system of nonlinear ODEs using the similarity transformations. The outcomes of the transformed equations have been achieved by using the bvp4c method in MATLAB software. Physical flow characteristics are shown against velocity, temperature, and entropy generation profiles. The velocity is declined for the greater values of volume fraction of nanoparticles and melting parameter. The thermal field is declined for the variations of thermal relaxation and melting parameters while boomed for the higher values of Biot number. The entropy generation profile is increased for the greater estimations of Reynolds number and Brinkman parameter. To the best of the researcher's information, no one has previously attempted to characterize melting phenomena and Cattaneo-Chrsitov heat theory applications by studying the flow through a nozzle of rocket engine using ( C o F e 2 O 4, C d T e, T i O 2, C u & C u O ) hybrid nanoparticles and kerosene ( C 12 H 26 − C 15 H 32 ) as a base fluid.